Hand hygiene practices amongst patients - Prasad, Ashita; Ng Chok, Harrison; Wilkes, Lesley (International Journal of Infection Control, 2017)
Hand hygiene is seen as one of the principal means of preventing hospital based infections for both staff and patients. While there are many guidelines for hand hygiene practices for health professionals, there is a scarcity of research studies about the attitudes and hand hygiene practices among patients. The aim of this study is to explore nurses and patient attitudes and behaviours towards patient hand hygiene at a tertiary teaching hospital in Western Sydney. This descriptive study used patient observations of hand hygiene practices using a validated observation tool; face-to-face interviews with patients and a survey of nurses. Interviews and surveys were textually and quantitatively analysed. A total of 105 patient observations, 50 patient interviews and 51 nurse surveys were collected. The majority of patients and nurses respectively reported hand hygiene as an important aspect of everyday life in preventing infection in the hospital setting. However, this contrasts with the poor patient hand hygiene compliance identified using the patient observation tool. Patient interviews found that more encouragement and education by staff, increased signage and easily accessible facilities will increase hand hygiene practices. This study highlights the importance of patient input in understanding the entirety of hand hygiene practice from both the nurses and patients point of view. Further training of nursing staff in promoting a hand hygiene friendly environment will have a powerful influence among patients and in delivering patient centred care.